The impact of an ageing population on economic growth: an exploratory review of the main mechanisms - Nagarajan,N. Renuga (2016)
Although a myriad of important theoretical and empirical contributions on ageing populations exist, these are diffuse and lack an integrated vision of the distinct mechanisms through which ageing populations affect economic growth. This being the case, in this paper we survey the literature that provides insights regarding the ageing population and its effect on economic growth. In particular, we seek to uncover the main mechanisms by which ageing affects economic growth.